Recent advances in sustainable and safe marine engine operation with alternative fuels - Karvounis, Panagiotis; Tsoumpris, Charalampos; Boulougouris, Evangelos; Theotokatos, Gerasimos (Frontiers in Mechanical Engineering, 2022)
Pursuing net-zero emissions operations of the shipping industry are quintessential for mitigating this sector the environmental impact caused by the hydrocarbon fuels combustion. Significant contributions are expected from the substitution of the conventional marine fuels by alternative, emissions-free ones with lower emissions footprint. This study aim is to conduct a comprehensive literature review for delineating the main characteristics of the alternative considered fuels, focusing specifically on hydrogen, methanol and ammonia, which recently attracted attention by both the industry and academia. This study comparatively assesses the potential for using these fuels in marine engines and their subsequent performance characteristics, as well as the associated environmental benefits. In addition, the required storage conditions and space as well as the associated costs are reviewed. Special attention is given to the safety characteristics and requirements for each alternative fuel. This study results demonstrate that the environmental benefits from the alternative fuels use are pronounced only when renewable energy is considerably exploited for their production, whereas each fuel feasibility depends on the vessel type and the pertinent storage constraints. Hydrogen, ammonia and methanol, are considered best fit solution to small scale shipping that require minimal on-board storage. In addition, the need for comparative assessments between diesel and alternative fuels is highlighted to shed light on the marine engines operational characteristics. Moreover, jointly using alternative and diesel fuels is identified as a direction towards the transition of the maritime sector decarbonisation, which intensifies the need for optimisation studies of marine engines design and operation. This study concludes with recommendations for future research directions, thus contributing to fuel research concepts for facilitating the shipboard use of alternative fuels.